An Ultra-Low-Voltage Single-Crystal Oscillator-Timer (XO-Timer) Delivering 16-MHz and 32.258-kHz Clocks for Sub-0.5-V Energy-Harvesting BLE Radios in 28-nm CMOS - Liwen Lin; Ka-Meng Lei; Pui-In Mak; Rui P. Martins (IEEE Open Journal of Circuits and Systems, 2023)
This paper reports an ultra-low-voltage (ULV) single-crystal oscillator-timer (XO-Timer) for sub-0.5 V Bluetooth low-energy (BLE) radios that aims for self-powering by harvesting the ambient energies. Specifically, we tailor an on-chip micropower manager $(μ $ PM) to customize the voltage and current budgets for each sub-function of the XO-Timer. Such $μ $ PM shows a high power efficiency by introducing a 3-stage cascaded structure and a single voltage-regulation loop; they together uphold the performance of the XO-Timer amid supply-voltage and temperature variations. The core amplifier of the XO-Timer is ULV-enabled, and is reconfigurable (i.e., 1-stage and 3-stage gm) to balance between the power budget and performance under the high-performance mode (HPM) and low-power mode (LPM). Fabricated in 28-nm CMOS, the XO-Timer in HPM generates a 16-MHz clock with a power of $24.3 ~μ \text{W}$ , and a phase noise of −133.8 dBc/Hz at 1-kHz offset, resulting in a Figure-of-Merit (FoM1) of −236 dBc/Hz. In the LPM, the XO-Timer delivers a 32.258-kHz clock while consuming $11.4 ~μ \text{W}$ . The sleep-timer FoM2 is $14.8 ~μ \text{W}$ and the Allan deviation is 35.1 ppb, achieving the lowest supply voltage (0.25 V) not only for a dual-mode XO-Timer but also for a MHz-range XO.